Geometry Characterization of Products Results in the Finishing Process Using Centerless Belt Grinding Machine - Jesika Erventy Osman; Sofia Debi Puspa; Triyono; Hary Munandar (Fakultas Teknik Universitas Pancasila, 2024)
The centerless belt grinding machine that was previously designed at the Department of Mechanical Engineering at Universitas Trisakti can be used for finishing machining products. However, it is not yet known how the machine will perform on the geometric characteristics of the product as a result of the finishing process with a centerless belt grinding machine. The geometric characteristics here are the results of measurements in cylindricality, roundness, and surface roughness. This research aims to determine the machine's performance and whether there are significant differences in the centerless belt grinding finishing process. Control chart analysis is used to determine the consistency of engine performance, and a comparison of the feed speed is used to determine engine performance. Next, data processing was carried out using the paired sample t-test statistical test to determine whether there were significant differences between the turning and milling processes. The consistency test results indicated good performance achieved at a maximum speed of 25.47 mm/minute (angle 12°) for cylindrical, roundness, and surface roughness measurements. The statistical test results of the paired t-test between the turning and grinding processes showed significant differences, as indicated by the P-value (0.00) < ∝ (0.05) on cylindricality, roundness, and surface roughness.